Edukasi Pencegahan dan Penanganan ISPA pada Balita untuk Meningkatkan Kesehatan Keluarga - Swasti, Ni Komang; Natalia, Omiati (CV Putra Publisher, 2025)
Acute Respiratory Infections (ARI) continue to be a major challenge in child health, particularly among toddlers, with a significant contribution to morbidity and mortality rates. In Indonesia, ARI is the leading cause of pediatric hospital admissions, with environmental factors such as air pollution, cigarette smoke, and poor sanitation exacerbating the condition. In Central Lombok Regency, data from the Pringgarata Health Center show that around 40% of toddlers experience ARI symptoms, which often develop into pneumonia due to delayed treatment. Parents' knowledge of early symptoms and prevention of ARI is still limited, highlighting the need for effective educational efforts. The aim of this community service project is to increase parents' knowledge about ARI, including its symptoms, risk factors, and preventive measures, through educational leaflets. The method used is a descriptive quantitative approach with pre-test and post-test to measure improvements in parents' knowledge. The results showed a significant increase in knowledge among the majority of respondents after participating in the educational session. Before the education, 64% of respondents had poor knowledge, but after the education, 79% showed good understanding. In conclusion, leaflet-based education is effective in improving parents' knowledge about ARI and can be applied as a preventive measure to reduce the incidence of ARI in toddlers. It is recommended to conduct ongoing education to raise public awareness about the importance of ARI prevention.